Androgen potentiates the expression of FSH receptor and supports preantral follicle development in mice - Yuya Fujibe; Tsuyoshi Baba; Sachiko Nagao; Sayaka Adachi; Keiko Ikeda; Miyuki Morishita; Yoshika Kuno; Masahiro Suzuki; Masahito Mizuuchi; Hiroyuki Honnma; Toshiaki Endo; Tsuyoshi Saito (BMC, 2019)
Abstract Hyperandrogenism is one of the cardinal symptoms in polycystic ovary syndrome and plays a key role in the pathogenesis of polycystic ovary syndrome. However, the precise effects and mechanisms of excess androgen during follicular development are still unclear. Here we investigated the effects of androgen on mouse follicle development in vitro. Androgen did not affect the growth of follicles smaller than 160-180 μm in the presence of follicle-stimulating hormone (FSH). However, in the presence of low FSH, androgen supported the growth of follicles larger than 160-180 μm, a size at which growing follicles acquire FSH-dependency. Androgen did not change the mRNA expression of various growth-promoting factors but did increase mRNA expression of the FSH receptor. We suggest that androgen has a positive impact on follicle development by augmentation of the actions of FSH. Therefore, FSH-responsive but FSH-independent follicles grow in the presence of a certain level of FSH or androgen, and androgen compensates for FSH deficiency in FSH-dependent follicles.